Case report: Preventive infusion of donor-derived CD7 chimeric antigen receptor T cells after allogeneic hematopoietic stem cell transplantation - Jiang, Ying; Feng, Dan; Zhu, Jun; Wei, Daolin; Zhao, Chuxian; Liu, Huixia; Shao, Shan; Wang, Chun (Frontiers in Immunology, 2024)
Chimeric antigen receptor T cells (CAR T) targeting CD7 for T-cell acute lymphoblastic leukemia/lymphoma (T-ALL/LBL) showed promising efficacy and safety in some clinical trials. However, most of them were bridged with allogeneic hematopoietic stem cell transplantation (allo-HSCT). We described successful treatment with preventive donor-derived anti-CD7 CAR-T therapy in a case of refractory T lymphoblastic lymphoma following allo-HSCT, who could not receive autologous anti-CD7 CAR-T products due to the low-quality of T lymphocytes. To date, the patient’s complete remission has persisted for 20 months after HSCT.